Association between HLA alleles and beta-lactam antibiotics-related severe cutaneous adverse reactions - Wattanachai, Pansakon; Amornpinyo, Warayuwadee; Konyoung, Parinya; Purimart, Danklai; Khunarkornsiri, Usanee; Pattanacheewapull, Oranuch; Tassaneeyakul, Wichittra; Nakkam, Nontaya (Frontiers in Pharmacology, 2023)
Introduction: Beta-lactam antibiotics are one of the most common causes of antibiotics-related severe cutaneous adverse reactions (SCARs) including Stevens–Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), drug reactions with eosinophilia and systemic symptoms (DRESS), and acute generalized exanthematous pustulosis (AGEP). Recent evidence demonstrated that the human leukocyte antigen (HLA) polymorphisms play important roles in the development of drug-related SCARs. This study aimed to extensively characterize the associations between HLA genetic polymorphisms and several phenotypes of SCARs related to beta-lactam antibiotics. Methods: Thirty-one Thai patients with beta-lactam antibiotics-related SCARs were enrolled in the study. A total of 183 unrelated native Thai subjects without any evidence of drug allergy were recruited as the control group. Genotyping of HLA class I and class II alleles was performed. Results: Six HLA alleles including HLA-A*01:01, HLA-B*50:01, HLA-C*06:02, HLA-DRB1*15:01, HLA-DQA1*03:01, and HLA-DQB1*03:02, were significantly associated with beta-lactam antibiotics-related SCARs. The highest risk of SCARs was observed in patients with the HLA-B*50:01 allele (OR = 12.6, 95% CI = 1.1–142.9, p = 0.042), followed by the HLA-DQB1*03:02 allele (OR = 5.8, 95% CI = 1.5–22.0, p = 0.012) and the HLA-C*06:02 allele (OR = 5.7, 95% CI = 1.6–19.9, p = 0.011). According to the phenotypes of SCARs related to beta-lactam antibiotics, the higher risk of SJS/TEN was observed in patients with HLA-A*03:02, HLA-B*46:02 (OR = 17.5, 95% CI = 1.5–201.6, p = 0.033), HLA-A*02:06, HLA-B*57:01 (OR = 9.5, 95% CI = 1.3–71.5, p = 0.028), HLA-DQB1*03:02 (OR = 7.5, 95% CI = 1.8–30.9, p = 0.008), or HLA-C*06:02 (OR = 4.9, 95% CI = 1.1–21.4, p = 0.008). While eight HLA alleles including HLA-A*02:05, HLA-A*02:11, HLA-B*37:01, HLA-B*38:01, HLA-B*50:01, HLA-C*06:02, HLA-C*03:09, and HLA-DRB1*15:01 were associated with AGEP, the highest risk of AGEP was observed in patients with the HLA-B*50:01 allele (OR = 60.7, 95% CI = 4.8–765.00, p = 0.005). Among the four HLA alleles associated with DRESS including HLA-C*04:06, HLA-DRB1*04:05, HLA-DRB1*11:01, and HLA-DQB1*04:01, the HLA-C*04:06 allele had the highest risk of beta-lactam antibiotics-related DRESS (OR = 60.0, 95% CI = 3.0–1202.1, p = 0.043). However, these associations did not achieve statistical significance after Bonferroni’s correction. Apart from the HLA risk alleles, the HLA-A*02:07 allele appeared to be a protective factor against beta-lactam antibiotic-related SCARs (OR = 0.1, 95% CI = 0.0–0.5, p = 3.7 × 10−4, Pc = 0.012). Conclusion: This study demonstrated the candidate HLA alleles that are significantly associated with several phenotypes of beta-lactam antibiotics-related SCARs. However, whether the HLA alleles observed in this study can be used as valid genetic markers for SCARs related to beta-lactam antibiotics needs to be further explored in other ethnicities and larger cohort studies.